2021
DOI: 10.5937/ratpov58-33346
|View full text |Cite
|
Sign up to set email alerts
|

Chamomile essential oil quality after postharvest separation treatments

Abstract: Ecological conditions of the growing areas, growing practices as well as harvest and postharvest processing influence the yield and quality of chamomile. The aim of this research was to determine the influence of chamomile separation methods, as postharvest treatments, on the essential oil quality and content, with a view to improve current primary processing of this valuable medicinal plant. In order to explain the structure of laboratory data that would give deeper assessment of similarities among various sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The most abundant volatile compound found in chamomile flowers was Spiroether Z (ZSPI). Similar results were obtained by Aćimović et al (2021) [38]. ZSPI did not change significantly in SUN, SH, and KK60 samples (34-36%), but decreased significantly after flower drying at high temperature (D sample, to 28%).…”
Section: Volatile Compounds Extracted By N-hexanesupporting
confidence: 83%
See 1 more Smart Citation
“…The most abundant volatile compound found in chamomile flowers was Spiroether Z (ZSPI). Similar results were obtained by Aćimović et al (2021) [38]. ZSPI did not change significantly in SUN, SH, and KK60 samples (34-36%), but decreased significantly after flower drying at high temperature (D sample, to 28%).…”
Section: Volatile Compounds Extracted By N-hexanesupporting
confidence: 83%
“…GC-MS analysis of chamomile essential oil identified 49 compounds in total (Figure 5). Salamon et al (2023) [37] recorded between 23 and 43 chemical components in the essential oil extracted from chamomile flowers in different sites in Albania, and Aćimović et al (2021) [38] between 47 and 57 chemical components in essential oil. The most abundant compounds in all samples are α-bisabolol oxide A (ABOLA) (19.6 to 24.3%), bisabolol oxide B (BIOB) (19.3 to 23.2%), and β-farnesene E (BFAR) (15.9 to 25.5%).…”
Section: Essential Oilsmentioning
confidence: 98%
“…'Multimentha', in contrast to the first harvest, contained pulegone as the second most abundant compound with 18.55 ± 1.93% (sD) and 20.27 ± 1.35% (sF) and then the third highest fraction menthol isomer B with 9.26 ± 0.22% (sD) and 10.34 ± 0.27% (sF). Furthermore, it was hypothesized that the EO might be of higher quality when leaves and stems are separated prior to drying than after drying, because this would remove the water from the separated leaves more quickly and there would be less respiration and enzymatic processes [24]. The drying method impacts the phytochemical profile (e.g., in Lavendula angustifolia Mill.)…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…In their experiment, chamomile was dried immediately after harvest or separated between flowers and stems before drying. The study showed that the separation of chamomile in flowers and stems before drying had a significant effect on the content and composition of the EOs [24].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation